1998
DOI: 10.1577/1548-8667(1998)010<0211:sospio>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Salmonid Pathogens in Ocean-Caught Fishes in British Columbia, Canada

Abstract: A survey of wild fishes captured around marine net-pen salmon farms and from open waters for certain salmonid pathogens was conducted in the coastal waters of British Columbia. Viral hemorrhagic septicemia virus was detected in Pacific herring Clupea pallasi, shiner perch Cymatogaster aggregata, and threespine sticklebacks Gasterosteus aculeatus. Infectious hematopoietic necrosis (IHN) virus was detected in one Pacific herring (collected well away from the farms) and in tube-snouts Aulorhynchus flavidus and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 22 publications
1
79
1
1
Order By: Relevance
“…1), despite the fact that 579 herring and 605 sprat were sampled. In addition, 883 three-spined sticklebacks Gasterosteus aculeatus were sampled in the same area, without any VHSV isolations, a species from which VHSV has been isolated in North America (Kent et al 1998, Anonymous 2001. This is the first publication on sampling from the area north of Gotland.…”
Section: Vhsv Has Been Isolated From 2 Othermentioning
confidence: 99%
See 1 more Smart Citation
“…1), despite the fact that 579 herring and 605 sprat were sampled. In addition, 883 three-spined sticklebacks Gasterosteus aculeatus were sampled in the same area, without any VHSV isolations, a species from which VHSV has been isolated in North America (Kent et al 1998, Anonymous 2001. This is the first publication on sampling from the area north of Gotland.…”
Section: Vhsv Has Been Isolated From 2 Othermentioning
confidence: 99%
“…Since the first isolation from marine fish of viral haemorrhagic septicaemia virus (VHSV) from Atlantic cod Gadus morhua in 1979 (Jensen et al 1979, Jørgensen & Olesen 1987, VHSV has been isolated from an increasing number of marine fish species all over the northern hemisphere (Meyers & Winton 1995, Traxler et al 1995, Dixon et al 1997, Kent et al 1998, Mortensen et al 1999, Smail 2000, Takano et al 2000, Cox & Hedrick 2001, King et al 2001b, Kocan et al 2001, Brudeseth & Evensen 2002, Dopazo et al 2002, Olivier 2002, Watanabe et al 2002, Kim et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of IHNV from a single wild Pacific herring along the coast of British Columbia (Kent et al 1998) is an interesting observation and an unexpected finding when considering the results of our controlled studies. Higher localized IHNV exposure titers or extended waterborne exposure times in excess of 1 h may lead to rare infection in wild Pacific herring.…”
Section: Discussionmentioning
confidence: 73%
“…The virus has been detected in sockeye salmon at the end of their marine phase (Traxler et al 1997), and laboratory trials have demonstrated that Atlantic salmon develop IHN disease when cohabitated with IHNV-infected sockeye salmon (Traxler et al 1993). During a health survey of marine fish, IHNV was detected in 1 out of 289 wild Pacific herring in the marine waters of British Columbia (Kent et al 1998). However, there is only limited information regarding the susceptibility of Pacific herring to IHNV infection and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the epidemiology of this disease is not completely understood, most studies suggest that R. salmoninarum infects salmonines exclusively and that carrier fish are responsible for its distribution and transgenerational transmission (Wood and Yasutake, 1956;Bullock and Herman, 1988). Results from other studies, however, have indicated that nonsalmonine fish species such as the Pacific hake (Merluccius productus, Kent et al, 1998) and the Pacific herring (Clupea harengus pallasi, Paclibare et al, 1988) may harbor R. salmoninarum, but the potential role of nonsalmonid fish species in the epidemiology of BKD remains to be elucidated fully.…”
Section: Introductionmentioning
confidence: 98%